A QUALITATIVE STUDY OF TRUST AND PERCEIVED RISK OF ONLINE SHOPPING IN MANADO - Tamatompol, Elisa .; Pangemanan, Sifrid S.; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstact : Internet growth has a positive impact for business world. With the increase of online retailers on internet world, online shopping becomes popular. The purpose of this research is to analyze the trust issues and perceived risk of online shopping in Manado. This research used a descriptive study method was conducted qualitatively through in-depth interview with 10 respondent’s online shoppers in Manado. All the data and information gathered was analyzed using tri-angulations which data were gathered from the interview with difference informants, different place of observation, and review from several literatures of various researchers. The result of this research is trust and perceived risk affect online shopping, the higher consumer confidence against an existing site online will make them will often do online shopping, the smaller the risk though by consumers then the greater their decision to make a purchase online. So the online store must provide good service so that consumers continue to believe and will not feel aggrieved when shopping online.Keywords : trust, perceived risk, online shopping